Vaccine Refusal in the Czech Republic Is Associated with Being Spiritual but Not Religiously Affiliated - Kosarkova, Alice; Malinakova, Klara; van Dijk, Jitse P; Tavel, Peter (Vaccines, 2021)
A strong reduction in the deleterious effects of the COVID-19 pandemic can be achieved by vaccination. Religiosity and spirituality (R/S) may play an important role in vaccine acceptance. However, evidence is lacking for the associations with religious conspiracy theories (RCT) in a non-religious environment. This study investigated the associations between R/S and RCT about COVID-19 vaccination and the links of R/S with vaccine refusal and hesitancy. A sample of Czech adults (n = 459) participated in the survey. We measured R/S, RCT, religious fundamentalism, and COVID-19 vaccination intentions. We found spirituality to be significantly associated with RCT belief, with odds ratios (OR) of 2.12 (95% confidence interval [CI] 1.42-3.19). A combination of R/S groups revealed that spirituality with non-religious affiliation was associated with higher beliefs in RCT, with ORs from 3.51 to 7.17. Moreover, associations were found between spirituality with non-religious affiliation [OR 2.22(1.33-7.76)] with vaccine refusal. Our findings showed associations of spirituality and religious fundamentalism with RCT about COVID-19 vaccination. Furthermore, spirituality was linked to a higher possibility of vaccine refusal. Understanding these associations may help prevent the development of RCT and negative impact of spirituality on vaccine intentions and contribute to the effectiveness of the vaccination process.
Keywords: spirituality; religious conspiracy beliefs; vaccination; COVID-19 vaccine; religiosity